An overview of JAK/STAT pathways and JAK inhibition in alopecia areata - Lensing, Maddison; Jabbari, Ali (Frontiers in Immunology, 2022)
Alopecia Areata (AA) is a common autoimmune disease characterized by non-scarring hair loss ranging from patches on the scalp to complete hair loss involving the entire body. Disease onset is hypothesized to require the collapse of immune privilege of the hair follicle, which results in an increase in self-peptide/MHC expression along the follicular epithelium. Hair loss is associated with infiltration of the hair follicle with putatively self-reactive T cells. This process is thought to skew the hair follicle microenvironment away from a typically quiescent immune state towards one of active inflammation. This imbalance is mediated in part by the dominating presence of specific cytokines. While interferon- (IFN) has been identified as the key player in AA pathogenesis, many other cytokines have also been shown to play pivotal roles. Mechanistic studies in animal models have highlighted the contribution of common gamma chain (c) cytokines such as IL-2, IL-7, and IL-15 in augmenting disease. IFN and c cytokines signal through pathways involving receptor activation of Janus kinases (JAKs) and signal transducers and activators of transcription (STATs). Based on these findings, JAK/STAT pathways have been targeted for the purposes of therapeutic intervention in the clinical setting. Case reports and series have described use of small molecule JAK inhibitors leading to hair regrowth among AA patients. Furthermore, emerging clinical trial results show great promise and position JAK inhibitors as a treatment strategy for patients with severe or recalcitrant disease. Demonstrated efficacy from large-scale clinical trials of the JAK inhibitor baricitinib led to the first-in-disease FDA-approved treatment for AA in June of 2022. This review aims to highlight the JAK/STAT signaling pathways of various cytokines involved in AA and how targeting those pathways may impact disease outcomes in both laboratory and clinical settings.